PENGAMBILAN KEPUTUSAN NASABAH DALAM MEMBUKA REKENING BANK BSI DI LINGKUP MAHASISWA UHAMKA - Marsya Surinabila; Wanda Diah Pratiwi; Rahmawati Rahmawati; Krisna Ayuningtyas; Sri Rahayu; Budiandru Budiandru (Bajang Institute, 2023)
The purpose of this study was to find out the demand for Indonesian Islamic banks among UHAMKA students and to analyze customers' decisions in saving in Indonesian Sharia BANK. By using data Quantitative approach method. The data used are primary data and secondary data. The population in this study is 41 people. Determination of the sample is done by filling out the Google form link that has been distributed. The data analysis method uses the help of SPSS 22 software. Based on the results of our research that there is a connection with the customer's decision to open a BSI bank account that there is significant and the data that has been made valid.